2013
DOI: 10.1002/adhm.201300100
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Colorimetric Immunoassay Using a Nanocomposite Entrapping Magnetic and Platinum Nanoparticles in Ordered Mesoporous Carbon

Abstract: Nanocomposite to achieve ultrafast immunoassay: a new synergistically integrated nanocomposite consisting of magnetic and platinum nanoparticles, simultaneously entrapped in mesoporous carbon, is developed as a promising enzyme mimetic candidate to achieve ultrafast colorimetric immunoassays. Using new assay system, clinically important target molecules, such as human epidermal growth factor receptor 2 (HER2) and diarrhea-causing rotavirus, can be detected in only 3 min at room temperature with high specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…utilised the highly active peroxidase mimics, MNPs and platinum NPs, within porous carbon, as a signalling element for labelling with antibodies for the detection of human epidermal growth factor with a detection limit as low as 1.5 ng/mL when analysed using UV-vis spectroscopy. 19 The catalytic activity of Au NPs conjugated to antibodies has also been applied in an ELISA format. However, Wang et al reported that the catalytic activity was inhibited due to the addition of the protein molecules, but could be increased by the deposition of Au due to the formation of a new Au shell.…”
Section: Introductionmentioning
confidence: 99%
“…utilised the highly active peroxidase mimics, MNPs and platinum NPs, within porous carbon, as a signalling element for labelling with antibodies for the detection of human epidermal growth factor with a detection limit as low as 1.5 ng/mL when analysed using UV-vis spectroscopy. 19 The catalytic activity of Au NPs conjugated to antibodies has also been applied in an ELISA format. However, Wang et al reported that the catalytic activity was inhibited due to the addition of the protein molecules, but could be increased by the deposition of Au due to the formation of a new Au shell.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Qu et al, designed a heterogeneous palladium nanozyme that could effectively mediate the bioorthogonal reactions in situ through light and thus realized the specific imaging of mitochondria in living cells (Figures 2B,C). Beside CTCs and organelle imaging detection, there are also several other nanozymes-based colorimetric methods for specific disease imaging, including jaundice (Santhosh et al, 2014), acquired immune deficiency syndrome , diabetes (Tianran et al, 2014), infectious disease (Kim et al, 2014;Duan et al, 2015), and neurodegenerative disease (Wang C. I. et al, 2012;Farhadi et al, 2014). Thus, compared to traditional methods (such as PCR, cell flow cytometry, and ELISA), nanozymes methods exhibit more broaden prospect for live cell and organelle imaging because nanozyme assay is more fast, cost-effective and much easier to operate.…”
Section: Nanozymes For Live Cell and Organelle Imagingmentioning
confidence: 99%
“…10, 15 MNP are promising nanocatalysts because of their magnetic properties, high catalytic activity, and adjustability through nanoscale modifications 10, 1619 , suggesting possible uses in immunoassays 10, 13, 20, 21 , organic pollutant degradation 12, 2226 , glucose detection 17, 18, 2731 and cancer diagnostics. 14 Although it has been reported that MNP alone or combined with H 2 O 2 can prevent biofilm formation by inhibiting bacterial growth, 32, 33 there are no reports regarding the efficacy of an MNP-H 2 O 2 system on biofilm destruction and killing of bacteria resident within biofilms—a much more difficult medical challenge.…”
mentioning
confidence: 99%